Sonographic and histopathological correlation and evaluation of endometrium in perimenopausal women with abnormal uterine bleeding - Pillai, Shobha S. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Background: Abnormal Uterine Bleeding (AUB) in perimenopausal women accounts for about 70% of gynaecologic Outpatient Department visits. This assumes significance in view of the fact that AUB in this age group may be the only clinical sign of endometrial cancer. Objective of current study was to study the various types of menstrual abnormalities prevalent in perimenopausal women and to correlate the transvaginal ultrasonographic (TVUS) findings of endometrial thickness and pattern with the histopathological examination (HPE) of the Endometrium. Methods: Retrospective study was carried out on 88 women in the perimenopausal age group (40 to 51 years). All the women were clinically evaluated. TVUS study of endometrial pattern and thickness was done followed by Dilatation and Curettage (D&C) and HPE of the endometrial curettings. Results: From the sample set, 40% belonged to the age group of 48 to 51 years and 46.5% patients presented with menstrual complaints of menorrhagia, which accounts for the most common menstrual complaint. 70.5% of the patients in the study group were para 2 or less. Fibroid uterus was the commonest uterine pathology detected in 55.7% of the patients. 46.5% of patients had endometrial thickness in the range 5 to 9.9 mm. Most common finding on HPE was proliferative endometrium. 4.5% of cases revealed endometrial malignancy. Conclusions: In perimenopausal women with AUB, TVUS should be the investigation of choice due to its convenience, accuracy and non-invasiveness. In patients with hyperplastic endometrium and/ or endometrial thickness greater than 8 mm, a histopathological study of the endometrium is warranted to rule out atypical changes or endometrial malignancy.